Nanoscale lithium oxalate / carbon composite lithium supplement agent, preparation method and application of nanoscale lithium oxalate / carbon composite lithium supplement agent in lithium ion battery

By preparing nano-grade lithium oxalate/carbon composite lithium supplement agent, the problems of poor chemical stability and low decomposition efficiency of existing lithium supplement agents are solved, and efficient and stable lithium supplement effect of lithium-ion batteries are achieved, which is suitable for large-scale production.

CN119674077APending Publication Date: 2025-03-21NANJING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411820619.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Among the existing lithium-ion battery lithium supplement agents, the chemical stability of the ternary lithium-rich additives is poor and the reaction by-products remain after deliquification, and the large size of commercial lithium oxalate particles leads to low decomposition efficiency.

Method used

Using nano-grade lithium oxalate/carbon composite lithium supplement agent, nano-grade lithium oxalate powder is prepared into a saturated aqueous solution, and amphiphilic surfactant and carbon material are added, and then dried and ball milled to pulverize nano-grade lithium oxalate/carbon composite lithium supplement agent with excellent conductivity is prepared.

Benefits of technology

It improves the air stability and electrochemical performance of lithium supplements, reduces the deliquency potential, avoids side reactions, simplifies the process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674077A_ABST
    Figure CN119674077A_ABST
Patent Text Reader

Abstract

The invention discloses a nanoscale lithium oxalate / carbon composite lithium supplement agent, a preparation method and application of the nanoscale lithium oxalate / carbon composite lithium supplement agent in a lithium ion battery. The lithium oxalate powder is prepared into the lithium oxalate saturated aqueous solution, then the amphiphilic surfactant is added, overgrowth of crystals of the lithium oxalate in the drying process can be limited, the particle size of the lithium oxalate is effectively reduced, and therefore the ion transmission path is shortened. Besides, after the carbon material is added, the polar group of the amphiphilic surfactant promotes the uniform distribution of the carbon material, so that a three-dimensional conductive network structure is constructed, the electron transmission path is effectively shortened by the structure, and the conductivity of the material is remarkably improved. The lithium supplement agent prepared by the invention has remarkable electrochemical performance, and the decomposition potential of the lithium supplement agent is successfully reduced to about 4.33 V, which conforms to the working voltage range of a positive electrode material and an electrolyte of a commercial lithium ion battery. The method provided by the invention has the advantages of simple operation and no need of additional introduction of a metal catalyst, and can effectively reduce the raw material cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium supplementation of lithium batteries, and relates to a nano-scale lithium oxalate / carbon composite lithium supplementation agent, a preparation method and application thereof in lithium ion batteries. Background Art

[0002] Lithium-ion batteries have become one of the most popular types of rechargeable batteries due to their high energy density, long cycle life and low self-discharge rate, and will play a greater role in the future energy conversion and storage. However, the inevitable reaction leads to the formation of solid electrolyte interface (SEI), which causes the loss of active lithium ions, thus becoming the main reason for performance degradation.

[0003] As an innovative technology, lithium replenishment can provide additional lithium sources to compensate for capacity loss, thereby extending the life of lithium-ion batteries and improving their performance. Positive electrode lithium replenishment technology is gaining more and more attention due to its high compatibility with commercial lithium-ion battery manufacturing processes, especially its perfect integration with positive electrode preparation processes. Positive electrode lithium replenishers mainly include binary lithium-rich additives (such as Li2O, Li2S, Li3N, etc.) and ternary lithium-rich additives (such as Li5FeO4, Li2NiO2, Li2C2O4, etc.). Since Li5FeO4 and Li2NiO2 in ternary lithium-rich additives have higher specific capacity and suitable voltage platform, they have become the most commercialized lithium replenishers. However, they have the following two main problems: (1) poor chemical stability, exposure to humid air will cause increased interfacial impedance (2) residual reaction byproducts after delithiation.

[0004] Lithium oxalate (Li2C2O4) has excellent properties such as high theoretical capacity, low cost, air stability and no residue after delithiation, with a specific capacity of 525mAh g -1 , which makes it show wide application potential in lithium battery lithium supplement additives. However, the particle size of commercial Li2C2O4 is 20-30μm. When it is uniformly mixed with other solid components as a lithium supplement, the large particle size and insulation will limit the effective transfer of charge, resulting in its decomposition efficiency less than 20%, and the high lithium delithiation potential of 4.7V, which brings challenges to the positive electrode materials and electrolytes. Researchers usually enhance the ion and electron conductivity of materials by constructing conductive network structures, and introduce metal catalysts to reduce the reaction energy barrier and improve the overall activity. However, metal catalysts may cause the electrochemical reaction of positive electrode materials to be unstable, thereby inducing side reactions, and their synthesis process is complicated and costly. In addition, under high voltage conditions, metal catalysts may dissolve, which will affect the cycle life and safety of the battery. Therefore, the development of a low-cost and industrially adaptable positive electrode lithium supplement has become an important issue that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a nano-scale lithium oxalate / carbon composite lithium supplement, a preparation method and application thereof in lithium-ion batteries.

[0006] In a first aspect, the present invention provides a method for preparing a nano-scale lithium oxalate / carbon composite lithium supplement, comprising the following steps:

[0007] Lithium oxalate powder is added to deionized water to prepare a saturated aqueous solution of lithium oxalate, and then a certain proportion of amphiphilic surfactant is added to the solution, which is fully stirred, and then carbon material is added in a certain proportion, mixed evenly, and then dried, ball-milled, and crushed to obtain a nano-scale lithium oxalate / carbon composite lithium supplement with excellent conductivity.

[0008] Preferably, in the preparation method, lithium oxalate needs to be formulated into a saturated aqueous solution of lithium oxalate rather than directly using lithium oxalate powder. This is mainly because the particles of lithium oxalate powder are relatively large, resulting in a longer ion transmission path, thereby reducing the electrochemical properties of the material. Formulating it into a lithium oxalate solution can effectively control the crystal growth of lithium oxalate and improve the uniformity and particle size distribution of the material. At the same time, the saturated aqueous solution is beneficial to increasing the yield of nano-lithium oxalate.

[0009] Preferably, the amphiphilic surfactant is any one of carboxymethyl cellulose (CMC), polyvinyl pyrrolidone (PVP), alginic acid, etc.

[0010] Preferably, the carbon material is a conductive material for the positive electrode, preferably at least one of super conductive carbon black (SuperP Li), Ketjen black (KB), carbon nanotubes (CNT), activated carbon (AC), graphene (GR), etc.

[0011] Preferably, the mass ratio of the amphiphilic surfactant, the carbon material, and the lithium oxalate is (0.1-1):1:(1-3). The addition of the amphiphilic surfactant can inhibit the crystal growth of lithium oxalate during drying; at the same time, the polar groups of the amphiphilic surfactant promote the uniform distribution of the carbon material.

[0012] Preferably, the drying method is any one of ordinary drying, freeze drying, spray drying, etc., and the drying process has almost no effect on the performance of the lithium supplement.

[0013] Preferably, the particle size of the nano-scale lithium oxalate / carbon composite lithium supplement is 50-100 nm.

[0014] In a second aspect, the present invention provides a nano-scale lithium oxalate / carbon composite lithium supplement prepared by the method described in the first aspect.

[0015] In a third aspect, the present invention provides a use of a nano-scale lithium oxalate / carbon composite lithium supplement agent prepared by the method described in the first aspect as a positive electrode lithium supplement additive.

[0016] In a fourth aspect, the present invention provides a lithium-supplementing positive electrode active material, comprising a positive electrode active material and a nano-scale lithium oxalate / carbon composite lithium-supplementing agent prepared by the method described in the first aspect.

[0017] Preferably, the positive electrode active material is selected from any one of lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), ternary material (NMC / NCA), etc.

[0018] Preferably, the nano-scale lithium oxalate / carbon composite lithium replenisher is uniformly mixed with the positive electrode active material in a certain proportion, and the content of the nano-scale lithium oxalate / carbon composite lithium replenisher is 5% to 15wt% of the positive electrode active material, which is to ensure that the lithium sacrificed in the first cycle is fully replenished.

[0019] In a fifth aspect, the present invention provides a lithium-supplementing positive electrode material, comprising the lithium-supplementing positive electrode active material described in the fourth aspect, and further comprising a conductive agent and a binder.

[0020] In a sixth aspect, the present invention provides a lithium-supplemented positive electrode sheet, comprising a current collector and the lithium-supplemented positive electrode material according to the fifth aspect composited on the surface of the current collector.

[0021] Specifically, the nano-scale lithium oxalate / carbon composite lithium replenisher is evenly mixed with the positive electrode active material in a certain proportion to obtain a lithium replenishing positive electrode active material, and then the composite lithium replenisher is added into N-methylpyrrolidone (NMP) together with the conductive agent Super P Li and the binder polyvinylidene fluoride (PVDF) to perform a mixed slurry, which is then coated on the current collector carbon-coated aluminum foil, and then vacuum dried to obtain a positive electrode sheet containing the lithium replenisher, i.e., a lithium replenishing positive electrode sheet.

[0022] In a seventh aspect, the present invention further provides a lithium-ion battery comprising the nano-scale lithium oxalate / carbon composite lithium supplement prepared by the method described in the first aspect.

[0023] Preferably, it comprises the lithium-supplementing positive electrode active material described in the fourth aspect.

[0024] Preferably, it comprises the lithium-supplementing positive electrode material described in the fifth aspect.

[0025] Preferably, it comprises the lithium-supplemented positive electrode sheet described in the sixth aspect.

[0026] Compared with the prior art, the advantages of the present invention are:

[0027] 1. Compared with other ternary lithium-rich additives (such as Li5FeO4, Li2NiO2, etc.), the nano-scale lithium oxalate / carbon composite lithium supplement agent of the present invention has excellent air stability: it can effectively resist the influence of oxidation and moisture, extend storage and service life, and ensure good performance under various environmental conditions; no residue after delithiation: no harmful residue will be left during the delithiation process, avoiding the occurrence of side reactions.

[0028] 2. The lithium supplementation method of the present invention has a simple process: the addition of an amphiphilic surfactant can inhibit the crystal growth of lithium oxalate during drying, and promotes the dispersion of carbon materials and the uniform distribution of lithium oxalate, thereby reducing process complexity, which not only improves production efficiency but also reduces errors and risks that may occur during the production process.

[0029] 3. The lithium supplementation method of the present invention uses low raw material costs: reducing the overall production cost, making the technology more economically competitive in industrial applications and providing feasibility for large-scale production.

[0030] 4. The lithium replenishment method of the present invention does not require the addition of catalysts: metal catalysts may cause instability in the electrochemical reaction of the positive electrode material, thereby inducing side reactions. In addition, under high voltage conditions, metal catalysts may dissolve, thereby affecting the cycle life and safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of SP-2Li2C2O4 in Example 1.

[0032] Figure 2 This is the XRD diagram of SP-2Li2C2O4 in Example 1.

[0033] Figure 3 This is the charge and discharge curve of the Li||SP-2Li2C2O4 half-cell in Application Example 1.

[0034] Figure 4 This is the charge and discharge curve of the Li||SP-3Li2C2O4 half-cell in Application Example 1.

[0035] Figure 5 This is the charge and discharge curve of the Li||SP-Li2C2O4 half-cell in Application Example 1.

[0036] Figure 6 This is the voltage differential capacity diagram of the Li||SP-2Li2C2O4 half-cell in Application Example 1.

[0037] Figure 7 This is the charge and discharge curve of the Li||2(SP-2Li2C2O4) half-cell in Application Example 2.

[0038] Figure 8This is the charge and discharge curve of the Li||3(SP-2Li2C2O4) half-cell in Application Example 2.

[0039] Fig. 9 This is the charge and discharge curve of the Gra||LFP (SP-2Li2C2O4) full battery in Application Example 3.

[0040] Fig.10 This is the cycling performance diagram of the Gra||LFP (SP-2Li2C2O4) full battery in Application Example 3.

[0041] Fig.11 This is a scanning electron microscope image of commercial Li2C2O4.

[0042] Fig.12 This is the XRD pattern of commercial Li2C2O4.

[0043] Fig.13 For comparison, the charge and discharge curves of the Li||CM-Li2C2O4 half-cell in Application Example 1.

[0044] Fig.14 This is the voltage differential capacity diagram of the Li||CM-Li2C2O4 half-cell in comparative application example 1.

[0045] Fig.15 This is the charge and discharge curve of the Li||4(SP-2Li2C2O4) half-cell in comparative application example 2.

[0046] Fig.16 This is the charge and discharge curve of the Gra||LFP full battery in comparative application example 3.

[0047] Fig.17 This is a diagram for comparing the cycling performance of the Gra||LFP full battery in application example 3.

[0048] Fig.18 This is the charge and discharge curve of the Li||5(SP-2Li2C2O4) half-cell in comparative application example 3. DETAILED DESCRIPTION

[0049] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0050] Compared with the commonly used commercial positive lithium supplement, Li2C2O4 has excellent properties such as air stability and no residue after lithium removal, and its specific capacity is 525mAh g -1, but the particle size of commercial Li2C2O4 is 20-30μm. When it is uniformly mixed with other solid components and used as a lithium supplement, the larger particle size and insulation will limit the effective transfer of charge, resulting in a decomposition efficiency of less than 20%, and a high lithium delithiation potential of 4.7V, which poses challenges to the positive electrode materials and electrolytes. Researchers usually enhance the ion and electron conductivity of the material by constructing a conductive network structure, and introduce metal catalysts to reduce the reaction energy barrier and improve the overall activity. However, metal catalysts may cause the electrochemical reaction of the positive electrode material to be unstable, thereby inducing side reactions, and their synthesis process is complex and costly. In addition, under high voltage conditions, the metal catalyst may dissolve, thereby affecting the cycle life and safety of the battery. Based on this, the present invention prepares a nano-scale lithium oxalate / carbon composite material as a positive electrode lithium supplement. First, the lithium oxalate powder is prepared into a saturated aqueous solution of lithium oxalate, and then an amphiphilic surfactant is added. This process effectively reduces the particle size of lithium oxalate by limiting the growth of lithium oxalate crystals during the drying process, thereby shortening the ion transmission path. In addition, the polar groups of the amphiphilic surfactant promote the uniform distribution of the carbon material, thereby constructing a three-dimensional conductive network structure, which effectively shortens the electron transmission path and significantly improves the electrical conductivity of the material. The nanoscale lithium oxalate / carbon composite material prepared by this method has significant electrochemical properties, and its decomposition potential is successfully reduced to about 4.33V. This voltage platform is consistent with the operating voltage range of the positive electrode material and electrolyte of commercial lithium-ion batteries. The preparation method of the present invention has the advantages of simple operation and no need to introduce additional metal catalysts, which can effectively reduce the cost of raw materials. At the same time, the amphiphilic surfactant used not only optimizes the microstructure of the composite material, but also improves its electrochemical stability and conductivity. This technology has broad prospects for industrial application, is particularly suitable for large-scale production, and can provide important support for the long life and high performance applications of lithium-ion batteries.

[0051] The present invention provides a nano-scale lithium oxalate / carbon composite lithium supplement, a preparation method and application thereof in a lithium ion battery, comprising the following steps:

[0052] (1) Preparation method of positive electrode lithium supplement: amphiphilic surfactant, carbon material, Li2C2O4 are prepared in a mass ratio of (0.1-1):1:(1-3), firstly, lithium oxalate powder is added to deionized water to prepare a saturated aqueous solution of lithium oxalate, then a certain proportion of amphiphilic surfactant is added to the solution, and the mixture is stirred evenly. Then, carbon material is added in a certain proportion, mixed evenly, and dried, and then ball milled to obtain a nano-scale lithium oxalate / carbon composite lithium supplement with excellent conductivity.

[0053] (2) Preparation of positive electrode sheet containing lithium supplement agent: The nano-scale lithium oxalate / carbon composite lithium supplement agent obtained in step (1) is mixed with the positive electrode active material in a certain proportion, and then added to NMP together with Super P Li and PVDF for homogenization. The slurry is coated on carbon-coated aluminum foil and then vacuum dried to obtain a positive electrode sheet containing lithium supplement agent. The content of the nano-scale lithium oxalate / carbon composite lithium supplement agent is 5% to 15wt% of the content of the positive electrode active material.

[0054] In order to more clearly and in detail introduce the positive electrode sheet containing lithium supplement provided by the embodiment of the present invention, it will be described in combination with specific embodiments below.

[0055] Example 1

[0056] CMC, Super P Li, and Li2C2O4 were prepared in a mass ratio of 0.1:1:2. First, lithium oxalate powder was added to deionized water to prepare a saturated aqueous solution of lithium oxalate, and then CMC was added to the solution and stirred thoroughly. Then, carbon material Super P Li was added, mixed evenly, and dried. After ball milling, a nano-scale lithium oxalate / carbon composite lithium supplement with excellent conductivity and a particle size of 50-100nm was obtained, named SP-2Li2C2O4.

[0057] Figure 1 This is a scanning electron microscope image of SP-2Li2C2O4 prepared in Example 1. Figure 1 It can be seen that there is no large-sized Li2C2O4, indicating that Li2C2O4 is evenly distributed on the SP surface. At the same time, the cross-linked Super P Li constructs a conductive network structure, and the composite material particles are 50-100nm. Figure 2 shown.

[0058] Fig.11 This is a scanning electron microscope image of commercial Li2C2O4. Fig.11 It can be seen that the particle size is 20 to 40 μm. Fig.12 The XRD pattern of commercial Li2C2O4 is shown in Figure 2. Fig.12 It can be seen that commercial Li2C2O4 has good crystallinity, but the XRD diffraction peaks of SP-2Li2C2O4 ( Figure 2 ) is obviously broader than the XRD diffraction peak of commercial Li2C2O4. Therefore, it can be determined from the SEM and XRD patterns that the particle size of SP-2Li2C2O4 is significantly reduced.

[0059] Example 2

[0060] This embodiment is basically the same as the embodiment 1, except that the mass ratio of CMC, Super P Li, and Li2C2O4 is 0.1:1:3. The nano-scale lithium oxalate / carbon composite lithium supplement prepared in this embodiment is named SP-3Li2C2O4.

[0061] Example 3

[0062] This embodiment is basically the same as the embodiment 1, except that the mass ratio of CMC, Super P Li, and Li2C2O4 is 0.1:1:1. The nano-scale lithium oxalate / carbon composite lithium supplement prepared in this embodiment is named SP-Li2C2O4.

[0063] Example 4

[0064] This embodiment is basically the same as the embodiment 1, except that the drying method uses a common oven drying. The nano-scale lithium oxalate / carbon composite lithium supplement prepared in this embodiment is named 2 (SP-2Li2C2O4).

[0065] Example 5

[0066] This embodiment is basically the same as the embodiment 1, except that the drying method is spray drying. The nano-scale lithium oxalate / carbon composite lithium supplement prepared in this embodiment is named 3 (SP-2Li2C2O4).

[0067] Comparative Example 1

[0068] This embodiment is basically the same as Embodiment 1, except that no CMC is added, that is, the mass ratio of Super P Li to Li2C2O4 is 1:2, and it is named 4 (SP-2Li2C2O4).

[0069] Comparative Example 2

[0070] This embodiment is basically the same as the embodiment 1, except that Li2C2O4 powder is directly used, and CMC and Super P Li are added for ball milling. This embodiment is named 5 (SP-2Li2C2O4).

[0071] Application Example 1

[0072] The nano-scale lithium oxalate / carbon composite lithium supplement obtained in Examples 1 to 3 was mixed and homogenized with Super P Li and PVDF in a homogenizer at a mass ratio of 8:1:1. It was coated on aluminum foil, dried in an oven, cut, and assembled with lithium sheets in a vacuum glove box filled with argon to form half-cells, which were recorded as Li||SP-2Li2C2O4, Li||SP-3Li2C2O4, and Li||SP-Li2C2O4.

[0073] Figures 3 to 5 The charge and discharge curves of the half-cells Li||SP-2Li2C2O4, Li||SP-3Li2C2O4, and Li||SP-Li2C2O4 in this application example are shown in Figure 2. It can be seen that the charge specific capacities of the three half-cells are 543 mAh g -1 , 340mAh g -1 , 530mAh g -1 , from which it can be determined that the charge specific capacity of Li||SP-2Li2C2O4 and Li||SP-Li2C2O4 has reached the theoretical specific capacity of lithium oxalate, indicating that when the mass ratio of Super P Li to Li2C2O4 is 1:2, the decomposition efficiency of lithium oxalate reaches 100%.

[0074] Figure 6 The voltage differential capacity diagram of Li||SP-2Li2C2O4 half-cell is shown in Figure 2. Figure 6 It can be seen that the delithiation voltage platform is around 4.33V, which is suitable for lithium-ion battery positive electrode materials and electrolytes.

[0075] Application Example 2

[0076] The nano-scale lithium oxalate / carbon composite lithium supplement obtained in Examples 4 to 5 was mixed and homogenized with Super P Li and PVDF in a homogenizer at a mass ratio of 8:1:1. It was coated on aluminum foil, dried in an oven, cut, and assembled with lithium sheets in a vacuum glove box filled with argon to form half-cells, which were recorded as Li||2(SP-2Li2C2O4) and Li||3(SP-2Li2C2O4).

[0077] Figure 7 is the charge and discharge curve of Li||2(SP-2Li2C2O4) half-cell, from Figure 7 The charge and discharge capacity is 453mAh g -1 , the decomposition efficiency reached 86%. Figure 8 is the charge and discharge curve of Li||3(SP-2Li2C2O4) half-cell, from Figure 8 The charge and discharge capacity is 499mAh g -1 The decomposition efficiency reached 95%, and the delithiation voltage platform was around 4.3 V, indicating that the uniformly dispersed Super P Li constructed a conductive network structure and shortened the electron transmission path.

[0078] Comparative application example 1

[0079] Li2C2O4 was directly used as a lithium supplement and mixed with Super P Li and PVDF in a homogenizer at a mass ratio of 8:1:1. It was coated on aluminum foil and dried in an oven. After cutting, it was assembled with lithium sheets in a vacuum glove box filled with argon into a half-cell, which was recorded as Li||CM-Li2C2O4.

[0080] Fig.13 is the charge and discharge curve of Li||CM-Li2C2O4 half-cell, from Fig.13 The charge capacity is 21 mAhg -1 , which is far lower than the theoretical specific capacity (525 mAh g -1 ), the decomposition efficiency is 4%. Fig.14 The voltage differential capacity diagram of Li||CM-Li2C2O4 is shown in Figure 2. Fig.14 It can be seen that the delithiation voltage platform is around 4.65V, which is not suitable for lithium-ion battery positive electrode materials and electrolytes.

[0081] Comparative Application Example 2

[0082] 4(SP-2Li2C2O4) prepared in Comparative Example 1 was used as a lithium supplement and mixed with Super P Li and PVDF in a homogenizer at a mass ratio of 8:1:1. It was coated on aluminum foil, put into an oven for drying, cut into pieces, and assembled with lithium sheets in a vacuum glove box filled with argon into a half-cell, which was recorded as Li||4(SP-2Li2C2O4).

[0083] Fig.15 is the charge and discharge curve of Li||4(SP-2Li2C2O4) half-cell, from Fig.15 The charge capacity is 267 mAh g -1 , the decomposition efficiency is 51%. Compared with Li||CM-Li2C2O4 in comparative application example 1, the charge capacity is increased by 92%, indicating that Super P Li improves the conductivity of the composite material, but it is significantly lower than the charge capacity of the Li||SP-2Li2C2O4 half-cell in application example 1. This may be due to the fact that CMC was not added to the lithium supplement for preparing the Li||4 (SP-2Li2C2O4) half-cell, resulting in the aggregation and growth of lithium oxalate during the drying process, and the uneven dispersion of Super P Li, which affects the overall performance of the battery.

[0084] Comparative Application Example 3

[0085] 5(SP-2Li2C2O4) prepared in Comparative Example 2 was used as a lithium supplement and mixed with Super P Li and PVDF in a homogenizer at a mass ratio of 8:1:1. It was coated on aluminum foil, put into an oven for drying, cut into pieces, and assembled with lithium sheets in a vacuum glove box filled with argon into a half-cell, which was recorded as Li||5(SP-2Li2C2O4).

[0086] Fig.18 is the charge and discharge curve of Li||5(SP-2Li2C2O4) half-cell, from Fig.18 The charge capacity is 326 mAh g -1 , the decomposition efficiency is 62%. However, the specific capacity released at a voltage below 4.5 V is only 58.38 mAh g -1 , which is much lower than the Li||SP-2Li2C2O4 half-cell charge capacity in Application Example 1. This may be due to the large particles of the Li2C2O4 powder used, which may cause the ion diffusion path to become longer, thereby affecting the lithium ion release efficiency in the low voltage area.

[0087] Application Example 3

[0088] The positive electrode lithium supplement agent SP-2Li2C2O4 prepared in Example 1 was mixed with lithium iron phosphate (LFP) at a mass ratio of 1:9, and then mixed with Super P Li and PVDF in NMP at a mass ratio of 8:1:1. It was coated on a carbon-coated aluminum foil and then vacuum dried to obtain a lithium supplement positive electrode sheet, which was named LFP (SP-2Li2C2O4).

[0089] LFP (SP-2Li2C2O4) and the dried graphite negative electrode sheet were assembled into a full battery, denoted as Gra||LFP (SP-2Li2C2O4). Fig. 9 is the charge and discharge curve of Gra||LFP (SP-2Li2C2O4) full battery, from Fig. 9 As can be seen from the figure, the charge capacity of the full battery is 188 mAh g -1 , the discharge capacity is 155 mAh g -1 , Fig.10 This is the cycle performance diagram of the Gra||LFP (SP-2Li2C2O4) full battery. Fig.10 It can be seen that after 100 cycles, the discharge capacity is 122 mAh g -1 The average capacity decay rate per cycle is 0.2%.

[0090] Comparative Application Example 4

[0091] LFP, Super P Li and PVDF were mixed and slurried in NMP at a mass ratio of 8:1:1. Finally, it was coated on the electrode sheet and placed in a vacuum oven for drying to obtain a positive electrode sheet, which was named LFP.

[0092] LFP and the dried graphite negative electrode sheet are assembled into a full battery, denoted as Gra||LFP. Fig.16 is the charge and discharge curve of the Gra||LFP full battery. Fig.16 As can be seen from the figure, the charge capacity of the full battery is 163 mAh g -1 , the discharge capacity is 139 mAh g -1 Compared with the charge and discharge curve of the Gra||LFP (SP-2Li2C2O4) full battery in Application Example 3 ( Fig. 9 ), due to the addition of 10% positive electrode lithium supplement in the Gra||LFP (SP-2Li2C2O4) full battery, the first cycle charging capacity increased by 15% and the discharge capacity increased by 12%. This part of the increased capacity is provided by the active lithium released from lithium oxalate, which is used to provide the lithium consumed by the formation of SEI in the first cycle.

[0093] Fig.17 The cycle performance diagram of the Gra||LFP full battery is shown in Figure 2. Fig.17 It can be seen that after 100 cycles, the discharge capacity is 108 mAh g -1 The average capacity decay rate per cycle is 0.2%. Compared with the cycle performance diagram of the Gra||LFP (SP-2Li2C2O4) full battery in Application Example 3 ( Fig.10 ), the discharge capacity of Gra||LFP(SP-2Li2C2O4) full battery increased by 13% after 100 cycles.

Claims

1. A method for preparing a nano-scale lithium oxalate / carbon composite lithium supplement, characterized in that: The following steps are involved: The lithium oxalate powder is added to deionized water to prepare a saturated lithium oxalate aqueous solution, and then an amphiphilic surfactant is added to the solution, which is fully stirred, and then a carbon material is added, mixed evenly, and dried, and ball-milled to obtain a nano-scale lithium oxalate / carbon composite lithium supplement.

2. The method according to claim 1, characterized in that The amphiphilic surfactant is any one of carboxymethyl cellulose, polyvinyl pyrrolidone and alginic acid; the carbon material is at least one selected from ultra-dense high-conductive carbon black, Ketjen black, carbon nanotubes, activated carbon and graphene.

3. The method according to claim 1, characterized in that The mass ratio of amphiphilic surfactant, carbon material and lithium oxalate is (0.1~1):1:(1~3).

4. A nano-scale lithium oxalate / carbon composite lithium supplement prepared by the method according to any one of claims 1 to 3.

5. Use of the nano-scale lithium oxalate / carbon composite lithium supplement prepared by the method according to any one of claims 1 to 3 as a positive electrode lithium supplement additive.

6. A lithium-supplementing positive electrode active material, characterized in that: The invention comprises a positive electrode active material and also comprises a nano-scale lithium oxalate / carbon composite lithium supplement prepared by the method according to any one of claims 1 to 3.

7. The lithium-supplemented positive electrode active material according to claim 6, characterized in that: The content of nano-scale lithium oxalate / carbon composite lithium supplement is 5%~15wt% of the positive electrode active material content.

8. A lithium-supplementing positive electrode material, characterized in that: The invention comprises the lithium-supplementing positive electrode active material as claimed in claim 6 or 7, and further comprises a conductive agent and a binder.

9. A lithium-supplemented positive electrode sheet, characterized in that: It comprises a current collector and a lithium-supplementing positive electrode material as claimed in claim 89 composited on the surface of the current collector.

10. A lithium ion battery, characterized in that: The invention relates to a nano-scale lithium oxalate / carbon composite lithium supplement prepared by the method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Lithium nickel manganese oxide battery positive electrode method

    CN108365215A

  • Lithium supplementing slurry with core-shell structure and application of lithium supplementing slurry to lithium supplementing modification of positive electrode of lithium ion battery

    CN112038639A

  • Positive electrode lithium supplementing material, preparation method and application thereof

    CN115911610A

  • Composite lithium supplementing material and preparation method thereof, lithium supplementing coating and preparation method thereof, and lithium battery

    CN116799210A

  • Lithium supplement material and preparation method thereof, positive electrode material and secondary battery

    CN118039905A

Cited By

  • A nanoscale sodium oxalate / carbon composite sodium supplement, a preparation method thereof and application thereof in sodium ion batteries

    CN122907638A